Perbandingan Hasil Belajar IPS Terpadu Model Pembelajaran Kooperatif Tipe Two Stay-Two Stray Dengan Metode Ceramah - Sumiyati Sumiyati; Nurjannah Nurjannah; Husnul Khotimah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2017)
[Title: Comparison of Integrated IPS Learning Outcomes Cooperative Learning Model Type Two Stay-Two Stray With Lecture Method] This study aims to develop student learning outcomes using the Two Stay-Two Stray type cooperative learning model. The research method used is a quantitative method. The results showed that there were differences in the learning outcomes of the cooperative learning model type two stay-two stray with conventional methods in integrated social studies subjects of class VIII of SMP Negeri 4 Dompu in the 2016/2017 learning year. The statement can be strengthened and proven by the results of data analysis using the T-test formula to produce a tcount of 0.651 compared to ttable of 0.249, it can be stated that there are differences in integrated social studies learning outcomes of students using cooperative learning type two stay-two stray with the Method The conventional class VIII of SMP Negeri 4 Dompu and the alternative hypothesis (Ha) proposed in this study were accepted.